2014
DOI: 10.1128/aac.03053-14
|View full text |Cite
|
Sign up to set email alerts
|

IS 5 Element Integration, a Novel Mechanism for Rapid In Vivo Emergence of Tigecycline Nonsusceptibility in Klebsiella pneumoniae

Abstract: dTigecycline nonsusceptibility is concerning because tigecycline is increasingly relied upon to treat carbapenem-or colistin-resistant organisms. In Enterobacteriaceae, tigecycline nonsusceptibility is mediated by the AcrAB-TolC efflux pump, among others, and pump activity is often a downstream effect of mutations in their transcriptional regulators, cognate repressor genes, or noncoding regions, as demonstrated in Enterobacteriaceae and Acinetobacter isolates. Here, we report the emergence of tigecycline nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…The relative expression of each target gene was then calibrated against the corresponding expression of a tigecycline-susceptible K. pneumoniae KP478, which served as reference strain (expression ϭ 1; tigecycline MIC, 0.25 mg/liter). Specific primers for the aforementioned genes are listed in Table S1 in the supplemental material (20)(21)(22). The experiments were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…The relative expression of each target gene was then calibrated against the corresponding expression of a tigecycline-susceptible K. pneumoniae KP478, which served as reference strain (expression ϭ 1; tigecycline MIC, 0.25 mg/liter). Specific primers for the aforementioned genes are listed in Table S1 in the supplemental material (20)(21)(22). The experiments were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, recently showed that rarA upregulates, whereas oqxR downregulates, the expression of the OqxAB efflux pump system, which may also be a determining factor for tigecycline resistance. In addition, Nielsen et al (2014) found an IS5 insertion element in tigecycline-non-susceptible strains and named it the KpgABC efflux pump. Overexpression of kpgABC genes in non-kpgABC K. pneumoniae increased the MIC of tigecycline fourfold, independently of the AcrAB and OqxAB efflux pumps that contribute to tigecycline resistance (Nielsen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These results implied that other genetic regulative mechanisms of upregulated efflux pumps might be involved in regulation of gene expression and response to the bacteria exposed to antibiotics (Howden et al, 2013). Nielsen et al (2014) postulated that insertion of the IS5 integron might contribute to the increased expression levels AcrB fold expression change…”
mentioning
confidence: 97%
“…In addition to MDR mediated by the chromosomally encoded OqxAB pump (302)(303)(304), overexpression of the newly identified RND-type KpgABC pump was involved in tigecycline nonsusceptibility due to an IS element insertion in the promoter region of kpgABC (305). The KexD RND pump expressed by cloning provides MDR with the requirement of AcrA accessory and KocC OM proteins (306).…”
Section: Klebsiella Pneumoniaementioning
confidence: 99%